A Modular, Cost-Effective, and Pumpless Perfusion Assembly for the Long-Term Culture of Engineered Microvessels - Shashwat S. Agarwal; Jacob C. Holter; Travis H. Jones; Brendan T. Fuller; Joseph W. Tinapple; Joseph M. Barlage; Jonathan W. Song (Micromachines)
Continuous perfusion is necessary to sustain microphysiological systems and other microfluidic cell cultures. However, most of the established microfluidic perfusion systems, such as syringe pumps, peristaltic pumps, and rocker plates, have several operational challenges and may be cost-prohibitive, especially for laboratories with no microsystems engineering expertise. Here, we address the need for a cost-efficient, easy-to-implement, and reliable microfluidic perfusion system. Our solution is a modular pumpless perfusion assembly (PPA), which is constructed from commercially available, interchangeable, and aseptically packaged syringes and syringe filters. The total cost for the components of each assembled PPA is USD 1–2. The PPA retains the simplicity of gravity-based pumpless flow systems but incorporates high resistance filters that enable slow and sustained flow for extended periods of time (hours to days). The perfusion characteristics of the PPA were determined by theoretical calculations of the total hydraulic resistance of the assembly and experimental characterization of specific filter resistances. We demonstrated that the PPA enabled reliable long-term culture of engineered endothelialized 3-D microvessels for several weeks. Taken together, our novel PPA solution is simply constructed from extremely low-cost and commercially available laboratory supplies and facilitates robust cell culture and compatibility with current microfluidic setups.